By the Honourable James De Lancey, Esq ; His Majesty's lieutenant-governor, and commander in chief in and over the province of New-York ... A proclamation : Whereas by an act of the governor, Council and General Assembly of this province, entitled, An act for the better apprehending and securing deserters from His Majesty's forces in America, passed the ninth day of July, one thousand seven hundred and fifty six ... Given under my hand and seal at arms, at Fort-George, in the city of New-York, the first day of July, 1757 . (LLMC-digital (Series), 1757)
Enumerating the laws that pertain to the apprehension of alleged deserters from the Royal Army.